HBR guide to beating burnout (Harvard business review guides., 2021)
"Burnout is rampant. Recognize the signs and make the right changes now. The always-on workplace and increasing social pressures are leading to an unprecedented rate of burnout. Unmanaged, chronic work stress doesn't just lead to lower productivity and negative emotions--it can have dire personal and professional consequences. Are you and your team at risk? The HBR Guide to Beating Burnout provides practical tips and advice to help you and your team navigate the perils of workplace burnout and rediscover healthy engagement at work. You'll learn how to: recognize the risk factors, unravel the difference between being stressed and being burnt out, recognize the symptoms in yourself and others, understand how passion can lead to burnout, make the changes you need to make, now, return to productivity after burnout leads to apathy, help prevent burnout on your team, arm yourself with the advice you need to succeed on the job, with the most trusted brand in business"--